Análises espectral e simbólica da modulação autonômica cardíaca em repouso e em resposta à mudança postural de idosos saudáveis: comparação entre gêneros - Perseguini, Natália Maria (2010)
The dissertation consisted of two works. The objective of the first study was to use linear and non-linear methods to investigate the cardiac autonomic modulation in elderly men and women in response to a postural change from the supine to the standing position. Fourteen men (66 ± 3.5 years) and ten women (65 ± 3.3 years) who did not use hormonal replacement therapy (HRT) were evaluated. All volunteers were apparently healthy. The RR intervals (RRi) and the beat-to-beat heart rate (HR) were recorded in the supine and standing positions. The HR variability (HRV) was studied by spectral analysis: low frequency (LF) and high frequency (HF) in absolute units (LF and HF) and normalized units (LFun and HFun) as well as the low frequency/high frequency (LF/HF) ratio. Symbolic analysis (0V%, 1V%, 2LV% and 2ULV% indexes) and Shannon entropy were also calculated for the HRV analysis. Men presented higher LF, LFnu and LF/HF ratio, and lower HFnu and 1V% symbolic index when compared to women in the supine position. Shannon entropy was higher among men than among women in the standing position. During the postural change there were a decrease in LF and an increase in Shannon entropy in the men s group. There was an increase in LFnu and LH/HF ratio as well as a decrease in HF, HFnu and 2LV% symbolic index due to the postural change from supine to standing position in the women s group. In conclusion, women presented a more appropriate response to the postural change than men in the age range studied, showing that the cardiac autonomic modulation may be better preserved in women than in men. Similarly, the objective of the second study was to investigate the HR autonomic modulation in elderly men and women HRT users and no-users by linear and nonlinear methods. So, 15 men (66 ± 3.4 years), 13 women without HRT (64 ± 3.5 years) and 7 women HRT users (61 ± 2.1 years), all of them apparently healthy, were evaluated. The RRi and the beat-to-beat HR were recorded in the supine position. The data analysis was carried out on the same methods described in the first study. The cardiac autonomic modulation analysis in the supine position shows that the women without HRT presented higher HFnu and lower LFnu, LF/HF ratio and 0V% symbolic index when compared to the men. No differences were observed in the comparison between the women who used and did not use HRT. We concluded that the women without HRT seem to have a higher cardiac vagal modulation and a lower cardiac sympathetic modulation when compared to the men. The use of HRT may not offer advantages to the cardiac autonomic modulation in elderly women.